Shaping Smoking Cessation In Hard-To-Treat Smokers - Lamb, R.J. (2010)
OBJECTIVE: Contingency management (CM) can effectively treat addictions by providing abstinence incentives. However, CM fails for many who do not readily meet the abstinence criterion and earn incentives. Shaping may improve outcomes in these hard-to-treat (HTT) individuals, as shaping sets intermediate criteria for incentive delivery between the present behavior and total abstinence. This should result in HTT having improving rather than poor outcomes throughout treatment. We examined if shaping improved outcomes in HTT smokers (those never abstinent during a 10-visit baseline). METHOD: Smokers were stratified into HTT (n=96) and easier-to-treat (n=50; ETT – those abstinent at least once during baseline), and randomly assigned to either standard CM or shaping (CMS). CM provided incentives for breath carbon monoxide (CO) levels < 4 ppm (approximately 1-day of abstinence). CMS shaped abstinence by providing incentives for CO levels lower than the 7(th) lowest of the participant’s last 9 samples or < 4 ppm. Interventions lasted for 60 successive weekdays visits. RESULTS: Cluster analysis identified four groups of participants: stable successes; improving; deteriorating; and poor outcomes. In comparison to ETT, HTT were more likely to belong to one of the two unsuccessful clusters (odds ratio (OR)=8.1, 95% CI [3.1, 21]). This difference between the HTT and the ETT was greater with CM (OR=42 [5.9, 307]) than with CMS where the difference between HTT and ETT was not significant. Assignment to CMS predicted membership in the improving (P=0.002) as compared to the poor outcomes cluster. CONCLUSION: Shaping can increase the effectiveness of CM for HTT smokers.